Human Health Risk Assessment of Cd, Cu, Pb and Zn through Consumption of Raw and Pasteurized Cow's Milk - Soheil SOBHANARDAKANI (Tehran University of Medical Sciences, 2018)
Background: The analysis of the residual contents of heavy and toxic metals in foodstuff especially milk could be an important indicator of safety, quality, and level of pollution of the region in which the milk was produced. Therefore, the present investigation was carried out to assess human health risk of residues levels of four metals (Cd, Cu, Pb, and Zn) through consumption of raw and pasteurized cow's milk. Methods: In this analytical-observational study, totally 72 samples of raw and pasteurized cow's milk samples were collected from market basket of Hamadan City, western Iran in 2014. After preparation and processing the samples in the laboratory, the concentration of metals were determined using inductively coupled plasma (ICP-OES). Moreover, all statistical analyses were performed using the SPSS statistical package according to Shapiro-Wilk test for normality, One Way ANOVA (Duncan Multiple Range Test), Independent t-test and Pearson's correlations. Results: The mean concentrations (µg/kg) of Cd, Cu, Pb and Zn in raw milk samples were 0.36±0.28, 9.77±3.91, 32.83±20.80 and 253.70±87.96, respectively and in the pasteurized milk samples were 5.57±9.33, 8.41±5.99, 25.54±26.50 and 90.12±91.52, respectively. HRI values in adults and children via consumption of raw and pasteurized cow's milk were within the safe limits (HRI < 1). Conclusion: Considering the serious contamination of some samples of raw and pasteurized milk by Cd, Pb and Zn, a control of heavy metals content during the whole production processing of milk must be applied.